2015
DOI: 10.1016/j.ygyno.2015.05.040
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tumor growth of high-grade serous ovarian cancer cell lines

Abstract: Objective Genomic studies of ovarian cancer (OC) cell lines frequently used in research revealed that these cells do not fully represent high-grade serous ovarian cancer (HGSOC), the most common OC histologic type. However, OC lines that appear to genomically resemble HGSOC have not been extensively used and their growth characteristics in murine xenografts are essentially unknown. Methods To better understand growth patterns and characteristics of HGSOC cell lines in vivo, CAOV3, COV362, KURAMOCHI, NIH-OVCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 22 publications
13
154
2
Order By: Relevance
“…Consistent with previous reports, 13 we found that subcutaneous OVCAR-4 tumors grew slowly, but reliably in nude mice. Fluorescence imaging of the excised tumors from mice treated with fluorescent probe showed the same trend as the cell internalization studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous reports, 13 we found that subcutaneous OVCAR-4 tumors grew slowly, but reliably in nude mice. Fluorescence imaging of the excised tumors from mice treated with fluorescent probe showed the same trend as the cell internalization studies.…”
Section: Discussionsupporting
confidence: 93%
“…A recent in vivo study demonstrated the ability of this cell line to reliably form xenograft tumors in nude mice, suggesting that it as a promising experimental model for the ovarian cancer community. 13 However, the susceptibility of OVCAR-4 cells to the more common types of molecular targeting is not known. 14 …”
Section: Introductionmentioning
confidence: 99%
“…To determine TG2 expression in OCSCs, we used Q-RT-PCR and compared ALDH + /CD133 + and ALDH − /CD133 − cells FACS sorted from OVCAR5 and COV362, two representative HGSOC cell lines (25,26). TG2 m RNA expression was significantly increased in OCSCs compared to non-CSC (ALDH − /CD133 − Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PARP1 was deleted in UWB1.289 and OVCAR8 EOC cell lines that have reduced BRCA-1 expression through a deleterious mutation (UWB1.289) or promoter methylation (OVCAR8). These mutations are characterized elsewhere in the literature (46,47 radiography studies and analyzed data. HW designed CRISPR/ Cas9 guides for PARP-1 and performed in vitro PARP1-KO experiments.…”
Section: Methodsmentioning
confidence: 99%